Building spaces for sensitive perception - Corso, Vanessa (2024)
This article from the field of interdisciplinary technological poetics, discusses the sensorial aspect of the spectator's experience as a central factor in scenic design. The challenges faced and the procedures adopted in the process of creating O que se vê ao fechar os olhos are visited, a theatrical installation resulting from research-creation carried out in the master's degree in Performing Arts of the UFRGS Postgraduate Program. Faced with a world troubled by violence and climate catastrophes, there is a focus on the ordinary functional displacement of the bodies' senses as a means of fostering new ways of being and acting in the world, of stimulating a non-automated presence, of constituting a theatricality of the sensitive.